Application of a novel endocrine disruptor bisphenol A electrochemical sensor based on analogous heterostructure characteristics of La-doped Yb2O3 nanomaterials. Issue 43 (23rd October 2019) - Wang, Xiaojiao; Li, Yang; Zhou, Yuanzhen; He, Yijia
Abstract : The defect-abundant and smaller size of 3 wt% La–Yb2 O3 nanocrystal increased the density of electron transport tunnels and exhibited a stronger electrochemical response for BPA. Abstract : Bisphenol A (BPA) is one of the most prevalent environmental endocrine disrupting chemicals. In this present paper, a facile BPA sensor was successfully fabricated based on a La-doped Yb2 O3 nanorod modified carbon paste electrode (La–Yb2 O3 /CPE). La-doped Yb2 O3 nanorods were synthesized using a one step hydrothermal synthesis method and further investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and amperometric response analysis were applied to characterize the electrochemical properties of the sensor. Under the optimal conditions, the oxidation current increased linearly with increasing the concentration of BPA in the range of 0.04 to 15 μM with a detection limit of 0.013 μM. The prepared La-doped Yb2 O3 nanomaterial modified electrode showed good reproducibility, stability and anti-interference ability. Furthermore, this newly developed sensor was further adopted to measure BPA in tap water and milk samples. The possible electrocatalytic sensing mechanism is discussed.